If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying xi + x + i = 0 Reorder the terms: i + ix + x = 0 Solving i + ix + x = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-1x' to each side of the equation. i + ix + x + -1x = 0 + -1x Combine like terms: x + -1x = 0 i + ix + 0 = 0 + -1x i + ix = 0 + -1x Remove the zero: i + ix = -1x Combine like terms: -1x + x = 0 i + ix + x = 0 The solution to this equation could not be determined.
| (((x-9500000)/2)/x)=0.1 | | 17.3+x=43.2 | | 661.2=870 | | (((9500000-x)/2)/9500000)=0.1 | | (((1100000-x)/2)/1100000)=0.1 | | (((1200000-x)/2)/1200000)=0.1 | | 3h+320=10h | | 390/2,600 | | s*7-40=79 | | =10a+3b-8a-4b | | (((1350000-x)/2)/1350000)=0.1 | | (((1250000-x)/2)/1250000)=0.1 | | -12r-20=28 | | (((1300000-x)/2)/1300000)=0.08 | | X-0.3x=140 | | x/20=9/5 | | 5/7=x/49 | | 2x+19+5x+18+3x+17=184cm | | (n-8)-(-2n-2)= | | x+(x-2)+(x-4)+(x-6)=56 | | 49/98=x/112 | | x/60=40/50 | | x+x-2+x-4+x-6= | | 3x-12+x=4 | | 10.2x+0.8=22 | | 34(x-2)=2 | | f(n)=3f(n-1)-1 | | (((1300000-x)/2)/1300000)=0.1 | | 15=23-4m | | 14x+11=4x+11 | | h(-3)=3x-3 | | =11+0.9(y-10) |